First insights into using outline-based geometric morphometrics of wing cell contours to distinguish three morphologically similar species of Tabanus (Diptera: Tabanidae) - Tanasak Changbunjong; Thekhawet Weluwanarak; Tanawat Chaiphongpachara (Current Research in Parasitology and Vector-Borne Diseases)
Accurate species identification of horse flies (Diptera: Tabanidae) is crucial due to their role as vectors for various pathogens, which is essential for understanding their biology, devising strategies to control their populations, and enhancing disease surveillance. This study assessed the efficacy of outline-based geometric morphometrics (GM) by analyzing the wing cell contours of discal, first submarginal, and second submarginal cells to distinguish three morphologically similar Tabanus species commonly found in Thailand, T. megalops, T. rubidus, and T. striatus. Statistical analysis demonstrated significant size differences between T. rubidus and the two other species (P < 0.05), with T. rubidus exhibiting larger wing cells. Tabanus megalops and T. striatus had similar sizes; their size differences were not statistically significant. The accuracy of size analysis based on validated classification tests was relatively low, ranging from 64.67% to 68.67%. Nonetheless, all wing cell contours showed significant shape differences between the three species, as confirmed by Mahalanobis distance comparisons using 1000 permutation tests (P < 0.05). The shape of the first submarginal cell contour showed the highest classification accuracy (86.67%). Outline-based GM offers a significant advantage for analyzing fly specimens with incomplete wings that have intact cells. For damaged specimens, analyzing the contour of the first submarginal cell through this technique can be a viable alternative.